Exploring public service motivation in public organizations: A bibliometric analysis - Ali Roziqin; Yastinki Hasni Ivani; Rifki Muhammad Bintang; Parimal Kumar Roy; Apriyansyah Apriyansyah; M. Husni Tamrin (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
Public Service Motivation (PSM) plays an important role as the foundation of intrinsic values for public officials, influencing performance, integrity, service quality, and the effectiveness of organizations performance. The growing body of research on Public Service Motivation (PSM) in public organizations has attracted increasing interest from both practitioners and academics in the fields of public administration and governmental bureaucracy. This study aims to investigate scientific literature related to PSM indexed in the Scopus database using a bibliometric analysis approach. The bibliometric data were analyzed with the help of VOSviewer software. A total of 119 articles published between 1999 and 2023 were selected for inclusion in this review. PSM has been examined from various perspectives. Public Personnel Management is the journal that most frequently publishes studies on PSM in public organizations. Andersen, L.B. and Aarhus Universitet are identified as the most prolific author and institution, respectively, contributing to the field. Furthermore, the United States is the most prominent contributing country in PSM research. The VOSviewer analysis revealed five dominant thematic clusters within the literature on PSM in public organizations. Two themes that remain underexplored are work engagement and burnout. Therefore, future research could place greater emphasis on these areas, as well as on related themes such as turnover and organizational culture.